2017
DOI: 10.1039/c6cc09188a
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of concentric 2D multicomponent assemblies at the solution–solid interface

Abstract: We report on the design and fabrication of a four-component supramolecular network using the 'core-shell' approach. Each 'core' component templates the formation of an outer 'shell' leading to formation of three concentric 'shells' around the central guest. The 'shells' are formed only in presence of guests thus demonstrating remarkable selectivity in molecular recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 22 publications
(28 reference statements)
0
51
0
Order By: Relevance
“…For example, the cluster consisting of one coronene surrounded by six isophthalic acid can be embedded in the hexagonal DBA network via vdW interactions, leading to a three-component 2D crystal. 99 Later, a similar system was successful extended to drive formation of a four-component 2D crystal, 94,100 These demonstrations of multiple components co-adsorbed in selfassembled structure demonstrate the strict complementarity in size and shape for 2D host-guest complex formation, as well as the controlling influence of functionalization.…”
Section: Selective Binding Of Molecules In a Host-guest Structurementioning
confidence: 94%
“…For example, the cluster consisting of one coronene surrounded by six isophthalic acid can be embedded in the hexagonal DBA network via vdW interactions, leading to a three-component 2D crystal. 99 Later, a similar system was successful extended to drive formation of a four-component 2D crystal, 94,100 These demonstrations of multiple components co-adsorbed in selfassembled structure demonstrate the strict complementarity in size and shape for 2D host-guest complex formation, as well as the controlling influence of functionalization.…”
Section: Selective Binding Of Molecules In a Host-guest Structurementioning
confidence: 94%
“…As ac onsequence, the solution composition which leads to formation of ag iven multicomponent system,i sr arely the same as expected from the stoichiometry deduced from an ideal surface-adsorbedn etwork. [17] Besides the adsorption energy,t he relative solubility and intermolecular interactions are also at play in multicomponent coadsorption experiments. In the presentc ase, when equimolar quantities of the two components wereu sed, only phase separated patches of HBC1 and PDI were observed at the TCB/ HOPG interface (see Figure S8 Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, shape selection strategy emphasizes patterned dense packing of molecules strictly dictated by their shapes. Velpula et al [5] reported a four component host-guest network on highly oriented pyrolytic graphite (HOPG), where the guest coronene molecules were hosted by one shell of isophthalic acid molecules and two shells of differently sized dehydrobenzo [12]annulene molecules. Nevertheless, the uniformity of the SAMs was rather limited due to the lack of molecular selectivity.…”
Section: Surface Nanopatterning With Samsmentioning
confidence: 99%
“…[9] Otherwise, undesired defects could dominate the SAMs. [5,9] STM could in principle be used to screen the SAM formation conditions, but practically speaking, it may be inapplicable as STM measurement is generally rather time-consuming at ambient condition.…”
Section: Perspectivementioning
confidence: 99%